Optimal Financing and Dividend Strategies with Time Inconsistency in a Regime Switching Economy - Yehong Yang; Guohua Cao (Complexity)
This paper incorporates a manager’s time-inconsistent preferences into the unified dynamic q-theoretic framework to investigate their impact on the optimal external financing and dividend payout strategies in a regime switching economy. We find that with a higher degree of time inconsistency, either in a favorable market condition or in a financial crisis, dividends are paid out earlier and the equity issues are smaller in size in each occurrence; in a favorable market condition equity financing occurs particularly early. Hence, time inconsistency would result in a decreasing of a firm’s precautionary savings, which may directly cause capital chain rupture and make liquidation more likely. It also implies that corporate external financing and dividend payout are highly dependent on the degree of the manager’s time-inconsistent preferences in a regime switching economy.